The Effect of Aggregate Versus Per Capita Income Per Unit Ranking on Personal Income Size Distributions: Reply - Goldsmith, Selma F.; Jaszi, George; Kaitz, Hyman; Liebenberg, Maurice (The Review of Economics and Statistics, 1956)
Selma F. Goldsmith, George Jaszi, Hyman Kaitz, Maurice Liebenberg, The Effect of Aggregate Versus Per Capita Income Per Unit Ranking on Personal Income Size Distributions: Reply, The Review of Economics and Statistics, Vol. 38, No. 2 (May, 1956), p. 227